Representations of Sexual Harassment in the Film Please Be Quiet - Ardika, Ervito Rani; Adiprabowo, Vani Dias (Persepsi: Communication Journal, 2024)
This research uses John Fiske's semiotic approach to analyze the representation of sexual harassment in the film "Please Be Quiet". This research aims to understand how sexual harassment is represented in the narrative, images, and symbols in the film. By using interpretive analysis methods, this research reveals how depictions of sexual harassment in films influence viewers' understanding and perceptions. These findings provide insight into the implications of such representations in mass media and highlight the importance of continued research in understanding the role of the media in shaping society's views on sensitive issues such as sexual harassment. In conclusion, this analysis highlights the role of symbols in shaping individual experiences and social dynamics in the workplace, providing a deeper understanding of power dynamics, social construction of meaning, and class ideological differences in the context of social relations in the work environment.